System dynamics modelling for sensitivity analysis evaluation of driving factors on decoupled aquaponic systems in South Africa - Ayomoh, Michael (University of Pretoria, 2022)
Dissertation (MEng(Industrial and Systems Engineering))-- University of Pretoria, 2022.